A new geographic distribution and morphologic revision of Mastophorus muris (Nematoda: Spirurida), a parasite of the stomach of Rattus norvegicus in Rio de Janeiro, Brazil - Rapozo Dias, Ana Júlia (2024)
This study provides a comprehensive morphological redescription of Mastophorus muris Gmelin, 1790, a spirurid nematode, based on specimens collected from Rattus norvegicus Berkenhout, 1769 in Nova Iguaçu municipality, Rio de Janeiro, Brazil. Employing optical and scanning electron microscopy, we detailed morphological characteristics, including previously unreported features such as a pair of ad-cloacal papillae and details of pseudolabia teeth. Additionally, we report a new geographical distribution for M. muris in Brazil. The low prevalence of M. muris observed in this study highlights the potential impact of anthropic changes on parasite distribution. Further investigations, including molecular analyses, are necessary to elucidate the taxonomic complexity and host-parasite relationships within the genus Mastophorus